O estatuto da fantasia no corpus teórico freudiano - Souza, Pedro Fernandez de (2020)
The concept of fantasy was evidently a central point in what is conventionally called “the abandon of the seduction theory”: if until 1897 Freud considered to be true memories that which their patients told him and, as he theorized, lay at their symptom’s origin, henceforth the content of these reports loses the mnemonic status that it previously had, and the ensemble of the representations underlying the neurotic symptomatological formations is considered phantasmatic or even fictitious. Fact is that, although it is one of the major pivots of this theoretic turn of Freud, the concept of fantasy is no thematized by him as one of the epistemological pillars of the nascent theory, nominated psychoanalysis: in some of the moments of acutest theorization, it is not analysed, related to other concepts, nor it is questioned. On the other hand, fantasies pullulate in the analysis of clinical cases or aesthetic works, for example, that which reveals Freud as a skilful fantasies hunter at his analytical practice. In view of this apparent asymmetry, it was established as the main objective of this study to verify the epistemological status of the concept of fantasy within the Freudian theoretical corpus. In order to do so, we parted from the so-called “seduction theory”, summarizing it ant pointing out, within it, the role of three concepts: memory, symptom and desire. After that, we essayed to read and evaluate the theoretical metamorphosis operated with the advent of fantasy; for this, we returned to the three concepts chosen, now however within the psychoanalytical theory. Fantasy revealed to be fundamental (in the strong sense of the word) for understanding the truly psychoanalytical notions of memory, symptom and desire: without it, none of these terms can be comprehended in its entirety. We were able to diagnose, moreover, that it is precisely in virtue of its notable invisibility in the Freudian theoretical formalization that fantasy gains immeasurable importance there: even though it is not a theorization’s central figure, it emerges as a true irrecusable background of the Freudian text. It is as a horizon that fantasy peeps properly: just as it underlies the most varied conscious’ formations (symptoms, dreams, oblivions), it underlies the very meaning of the Freudian word as well. More than a psychoanalysis’ concept and object, for us fantasy represents both its most intimate truth and limit.